Facilitated Data Relay and Effects on Treatment of Severe Aortic Stenosis in Europe - Richard P. Steeds; Matthias Lutz; Jeetendra Thambyrajah; Antonio Serra; Eberhard Schulz; Jiri Maly; Marco Aiello; Tanja K. Rudolph; Guy Lloyd; Alessandro Santo Bortone; Karl Eugen Hauptmann; Alberto Clerici; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Many patients with severe aortic stenosis are referred late with advanced symptoms or inappropriately denied intervention. The objective was to investigate whether a structured communication to referring physicians (facilitated data relay) might improve the rate and timeliness of intervention. Methods and Results A prospective registry of consecutive patients with severe aortic stenosis at 23 centers in 9 European countries with transcatheter as well as surgical aortic valve replacement being available was performed. The study included a 3‐month documentation of the status quo (phase A), a 6‐month intervention phase (implementing facilitated data relay), and a 3‐month documentation of a legacy effect (phase‐B). Two thousand one hundred seventy‐one patients with severe aortic stenoses were enrolled (phase A: 759; intervention: 905; phase‐B: 507). Mean age was 77.9±10.0 years, and 80% were symptomatic, including 52% with severe symptoms. During phase A, intervention was planned in 464/696 (67%), 138 (20%) were assigned to watchful waiting, 8 (1%) to balloon aortic valvuloplasty, 60 (9%) were listed as not for active treatment, and in 26 (4%), no decision was made. Three hundred sixty‐three of 464 (78%) patients received the planned intervention within 3 months. Timeliness of the intervention improved as shown by the higher number of aortic valve replacements performed within 3 months (59% versus 51%, P=0.002) and a significant decrease in the time to intervention (36±38 versus 30±33 days, P=0.002). Conclusions A simple, low‐cost, facilitated data relay improves timeliness of treatment for patients diagnosed with severe aortic stenosis, resulting in a shorter time to transcatheter aortic valve replacement. This effect was mainly driven by a significant improvement in timeliness of intervention in transcatheter aortic valve replacement but not surgical aortic valve replacement. Clinical Trial Registration URL: https://www.clinicaltrials.gov/. Unique identifier: NCT02241447.